2008
DOI: 10.1073/pnas.0806632105
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the length of the carboxyl terminus mediate functional properties of neurokinin-1 receptor

Abstract: The neurokinin-1 receptor (NK1R) has two naturally occurring forms that differ in the length of the carboxyl terminus: a fulllength receptor consisting of 407 aa and a truncated receptor consisting of 311 aa. We examined whether there are differential signaling properties attributable to the carboxyl terminus of this receptor by using stably transfected human embryonic kidney (HEK293) cell lines that express either full-length or truncated NK1R. Substance P (SP) specifically triggered intracellular calcium inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(94 citation statements)
references
References 38 publications
2
92
0
Order By: Relevance
“…Treatment with an NK-1R antagonist reduced cyclooxygenase-2 expression as well as expression of the proliferation marker ki67 (21), showing a potential functional role for NK-1R (although not necessarily tr-NK-1R) in CAC. In addition, Lai et al (26) showed that upon ligand binding, tr-NK-1R, which lacks a C-terminal tail that binds and activates G q , cannot initiate calcium influx or activate PKC and NF-κB; however, the truncated receptor can activate ERK in a delayed manner. The tr-NK-1R has also been reported to be resistant to desensitization (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Treatment with an NK-1R antagonist reduced cyclooxygenase-2 expression as well as expression of the proliferation marker ki67 (21), showing a potential functional role for NK-1R (although not necessarily tr-NK-1R) in CAC. In addition, Lai et al (26) showed that upon ligand binding, tr-NK-1R, which lacks a C-terminal tail that binds and activates G q , cannot initiate calcium influx or activate PKC and NF-κB; however, the truncated receptor can activate ERK in a delayed manner. The tr-NK-1R has also been reported to be resistant to desensitization (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…tr-NK-1R is present in breast cancer tissue (24), and transfection of truncated but not full-length NK-1R into nontumorigenic breast epithelial cell lines creates a transformed phenotype with greatly increased growth capability (25). Signaling studies have shown that unlike fl-NK-1R, tr-NK-1R can neither initiate calcium influx via G q , nor activate PKC or NF-κB; however, ERK activation still occurs but at a slower rate (26). In light of these findings, we were particularly interested in examining the expression of tr-NK-1R in the transition from colonic inflammation to CAC.…”
mentioning
confidence: 99%
“…These isoforms have distinct signalling properties, with only the wild-type receptor being able to increase intracellular Ca 2+ concentration and activate the transcription factor NFκB, leading to increased expression of F o r R e v i e w O n l y mRNA for interleukin-8 [59]. In addition, compared to the wild-type receptor, the truncated NK 1 receptor variant may have an increased ability to interact with different G proteins, other GPCRs, or G protein-independent signalling pathways [59,63]. This could be of considerable importance in cells and tissues that have distinct expressions of the NK 1 receptor isoforms.…”
Section: Alternative Splicing Of Gpcr In Other Pathophysiological Conmentioning
confidence: 99%
“…[59][60][61][62][63][64] Neurokinin receptor 2 Exon exclusion Impaired ligand binding and signalling [65,66] Neuropeptide S receptor (GPRA) Alternative C-terminal exons, trancation Intracellular localization of truncated isoform [67] Opioid receptors Several Various Reviewed in [68] 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Overview of GPCRs encoded by more than one exon. In the "pre-human genome era" it was assumed that more than 90% of human GPCRs were intronless [15].…”
Section: Closing Remarksmentioning
confidence: 99%
“…Other mechanisms can regulate the duration of MAPK signals transmitted by the angiotensin AT1A receptor, including the dual specificity phosphatase MKP7, which interacts with ␤-arrestins and dephosphorylates JNK3 bound to ␤-arrestin2 (46). NK 1 R⌬325-407 interacts with ␤-arrestins only transiently (6,32). In contrast to the fulllength NK 1 R, ECE-1 inhibition did not cause retention of NK 1 R⌬325-407 with ␤-arrestins in endosomes and failed to cause sustained NK 1 R⌬325-407-mediated ERK2 activation.…”
Section: Ece-1 Degrades Sp In Endosomes Andmentioning
confidence: 99%